Preparation method of defluorination seed crystal material for pellet reactor

By using materials such as quartz sand and chitosan-based dispersion in the pellet reactor to prepare seed crystals, the problem of unstable crystallization effect in the prior art is solved, and efficient removal of fluoride ions in wastewater and calcium fluoride crystals are achieved. The recycling of the company has significant environmental and economic benefits.

CN119430429AActive Publication Date: 2025-02-14工大环境股份有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411639780.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing pellet reactor technology has unclear ideas for inducing crystal seed construction, unstable effects, and it is difficult to meet the industry's demand for efficient removal of fluoride ions in wastewater.

Method used

Using quartz sand, chitosan-based dispersion, tourmaline powder, dolomite powder, fluorite powder and other materials, the powder is evenly dispersed into the chitosan-based dispersion through spraying technology to form a spray coating material, and dried on the surface of quartz sand. , pellet reactor seeds with high bonding properties were prepared.

Benefits of technology

It realizes efficient removal of fluoride ions in wastewater, and at the same time generates high-purity calcium fluoride crystals, solving the problem of insufficient fluorite reserves and has important environmental and economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430429A_ABST
    Figure CN119430429A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of environmental engineering, in particular to a preparation method of a defluorination seed crystal material for a pellet reactor, which comprises the following steps: (1) preparing a chitosan-based dispersion liquid; (2) preparing materials; (3) dispersing and mixing; (4) spraying; (5) drying; the invention is mainly applied to the seed crystal for the pellet reactor, and the pellet reactor based on the seed crystal prepared by the invention can effectively remove fluorine ions in wastewater and recycle the generated calcium fluoride crystals, and has important environmental and economic values. The pellet reactor seed crystal material prepared by the invention is beneficial to meeting the industrial development and improving the environmental protection requirements, and promotes the application of the pellet reactor in the treatment of fluorine-containing wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental engineering, in particular to a method for preparing a fluorine removal seed material for a pellet reactor. Background Art

[0002] The wastewater generated in the production process of chemical, non-ferrous metal metallurgy, glass, electronics, electroplating and other industries often contains high concentrations of fluoride, which causes serious fluoride pollution to the water environment. Therefore, the treatment technology of fluoride-containing wastewater has always been a key research topic in the field of environmental protection. In recent years, with the improvement of environmental protection requirements and the development of industry, new progress has been made in the treatment technology of fluoride-containing wastewater. At present, in the treatment methods of fluoride-containing industrial wastewater at home and abroad, in addition to the traditional lime neutralization precipitation method and coagulation precipitation method, however, the lime neutralization precipitation method has problems such as difficulty in the sedimentation and separation of colloidal CaF2 precipitation, unstable fluoride ion concentration in the effluent, and high water content of CaF2 precipitate; the coagulation precipitation method has a narrow range of pH requirements for the dosing point, the fluoride ion removal effect is greatly affected by operational factors, the flocs are loose, the water content is high, and the cost of deep sludge treatment is high, which also affects the wide application of this method.

[0003] As a new type of fluoride removal technology, the pelletized crystal reactor (PCR) not only reduces the fluoride concentration in the water by inducing the crystallization of calcium fluoride in the water, but also generates high-purity calcium fluoride particles and reduces the production of by-products. In addition, the reserves of fluorite minerals required by my country's electrolytic aluminum, glass etching, fluorine chemical industry and other industries are insufficient. Fluorite has been listed as a national strategic resource, and more than 60% of fluorite ore needs to be imported. The developed PCR pellet technology can achieve efficient crystallization and recovery of fluorine elements, solve the problem of fluorine pollution, and realize the recovery of high-purity calcium fluoride (artificial fluorite), solving the problem of insufficient reserves of fluorite ore, a national strategic resource.

[0004] Currently, the ideas for constructing crystal seeds suitable for PCR-induced crystallization are unclear and the effects are unstable. In order to promote the development of PCR technology, the development of new pellet reactor seeds has important scientific research and economic value. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a method for preparing a fluorine-removing seed material for a pellet reactor.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a defluorination seed material for a pellet reactor comprises the following steps:

[0008] (1) preparing a chitosan-based dispersion;

[0009] (2) Preparation of materials:

[0010] Weigh respectively: quartz sand, tourmaline powder, dolomite powder, fluorite powder;

[0011] (3) Dispersion mixing:

[0012] Tourmaline powder, dolomite powder and fluorite powder are mixed to obtain a mixed powder, and the mixed powder is evenly dispersed in a chitosan-based dispersion to obtain a spray coating;

[0013] (4) Spraying:

[0014] Spraying the spray coating obtained in step (3) onto the surface of quartz sand;

[0015] (5) Drying:

[0016] The sprayed quartz sand is dried to obtain the product.

[0017] As a further technical solution, the chitosan-based dispersion preparation method is:

[0018] First, an acetic acid solution is added to a reaction kettle, and then the modified chitosan is added to the reaction kettle, and stirred at room temperature until the modified chitosan is completely dissolved to obtain a modified chitosan solution;

[0019] Weigh dopamine, prepare an alkaline aqueous solution, add dopamine to the alkaline aqueous solution, stir and mix for 20 minutes to obtain a dispersion, and keep it warm in an ice bath for later use;

[0020] The alkaline aqueous solution is a sodium hydroxide solution, and the pH value of the sodium hydroxide solution is 11;

[0021] The mass ratio of dopamine to alkaline aqueous solution is 12-15 g: 200 mL;

[0022] Adding the dispersion liquid and the additive to the modified chitosan solution, stirring and reacting for 8-10 hours at room temperature, to obtain a chitosan-based dispersion liquid;

[0023] The mixing mass ratio of the dispersion, the auxiliary agent and the modified chitosan solution is 3-5:0.1-0.16:15.

[0024] As a further technical solution, the modified chitosan solution is prepared as follows:

[0025] 15-17 g of modified chitosan was dissolved in 1% acetic acid solution to obtain 15-17% (w / v) modified chitosan solution.

[0026] As a further technical solution, the modified chitosan preparation method is:

[0027] First, 2 g of chitosan was dissolved in 1% acetic acid solution to obtain a 2% (w / v) chitosan solution;

[0028] Then, 3,4-dihydroxybenzaldehyde is added to the ethanol solution, and stirred to mix evenly to obtain a modified dispersion;

[0029] The mass fraction of the ethanol solution is 20%;

[0030] The mixing ratio of the 3,4-dihydroxybenzaldehyde and the ethanol solution is 0.15 g:10 mL;

[0031] The chitosan solution is added into the reactor, and then an inert gas is introduced into the reactor to exhaust the air in the reactor, and then the modified dispersion is obtained;

[0032] Wherein, the molar ratio of chitosan to 3,4-dihydroxybenzaldehyde in the chitosan solution is 1:1.

[0033] As a further technical solution, the inert gas is any one of nitrogen and neon.

[0034] As a further technical solution, the auxiliary agent is a cross-linking agent, an initiator and an accelerator;

[0035] Among them, the crosslinking agent is MBA, the initiator is APS, and the accelerator is TEMED;

[0036] Among them, the mixing mass ratio of the crosslinking agent, the initiator and the accelerator is 10:1:1.2.

[0037] As a further technical solution, the mass ratio of quartz sand: tourmaline powder: dolomite powder: fluorite powder is 80-90:1-3:1-5:5-9.

[0038] As a further technical solution, the particle size of the quartz sand is 0.2±0.1 mm.

[0039] As a further technical solution, the mixing ratio of the mixed powder and the chitosan-based dispersion is: 18-20g:150mL.

[0040] As a further technical solution, drying is as follows: the sprayed quartz sand is placed in a cool and ventilated place, and after natural drying, it is stored at room temperature.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The present invention is mainly applied to the crystal seeds used in the pellet reactor. The pellet reactor based on the crystal seeds prepared by the present invention can effectively remove fluoride ions in wastewater and recycle the generated calcium fluoride crystals, which has important environmental and economic value. The crystal seed material of the pellet reactor prepared by the present invention helps to meet the development of industry and the improvement of environmental protection requirements, and promotes the application of the pellet reactor in the treatment of fluoride-containing wastewater.

[0043] The pellet reactor seed material prepared by the present invention is made of quartz sand, chitosan-based dispersion, tourmaline powder, dolomite powder and fluorite powder. The quartz sand surface is sprayed with tourmaline powder, dolomite powder, fluorite powder and other powders uniformly on the quartz sand surface by using the spraying technology and utilizing the high viscosity of the chitosan-based dispersion. After the composite material is naturally dried, it is stored at room temperature. The seed has good chemical stability and can cope with various complex sewage environments.

[0044] Chitosan is derived from chitin widely present in nature and is obtained through deacetylation. It is a renewable resource and meets environmental protection requirements. The chitosan-based dispersion prepared by the present invention using chitosan as a raw material contains a large number of amino and hydroxyl functional groups in the polymer molecular structure. These functional groups enable chitosan to have a strong interaction between powders such as tourmaline powder, dolomite powder, fluorite powder and quartz sand through hydrogen bonds, ionic bonds or covalent bonds, thereby achieving a strong bonding effect. By introducing a variety of groups to modify chitosan, the bonding performance can be improved, so that higher bonding stability can be achieved in the process of preparing the seed material, and the comprehensive performance of the seed can be significantly improved.

[0045] The test shows that the color of the pellet reactor seed gradually changes from dark brown to grayish white over time. In addition, the opaque seed surface shows a gradually thickening transparent layer at the microscopic level, indicating that highly crystallized CaF2 crystals are effectively deposited on the pellet reactor seed. The thickness of the crystal layer of the pellet reactor seed can reach 0.018±0.003mm on the third day and 0.043±0.007mm on the sixth day. The crystallization kinetic formula is Y=0.0071*X-0.0009, which shows that the CaF2 crystals have a linear deposition trend on the pellet reactor seed, and the deposition rate can reach 7.1 microns / day, indicating that the pellet reactor seed has the kinetic performance that satisfies the efficient removal and enrichment of fluoride ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0047] Figure 1 A general diagram of the pellet reactor seed;

[0048] Figure 2 is a micrograph of the pellet reactor seed;

[0049] Figure 3 The morphology comparison of pellet reactor seeds that have not been crystallized, crystallized for 3 days, and crystallized for 6 days;

[0050] Figure 4 This is a characterization diagram of the crystallization kinetics of the pellet reactor seed;

[0051] Figure 5 Scanning electron micrograph of pellet reactor seeds after 6 days of crystallization. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] In the embodiment of the present invention, the activated sludge used is the activated sludge from the aeration tank of a municipal sewage treatment plant.

[0054] Example 1

[0055] A method for preparing a defluorination seed material for a pellet reactor comprises the following steps:

[0056] (1) preparing a chitosan-based dispersion;

[0057] (2) Preparation of materials:

[0058] Weigh respectively: quartz sand, tourmaline powder, dolomite powder, fluorite powder;

[0059] (3) Dispersion mixing:

[0060] Tourmaline powder, dolomite powder and fluorite powder are mixed to obtain a mixed powder, and the mixed powder is evenly dispersed in a chitosan-based dispersion to obtain a spray coating;

[0061] (4) Spraying:

[0062] Spraying the spray coating obtained in step (3) onto the surface of quartz sand;

[0063] (5) Drying:

[0064] The sprayed quartz sand is dried to obtain the product.

[0065] The chitosan-based dispersion is prepared by:

[0066] First, an acetic acid solution is added to a reaction kettle, and then the modified chitosan is added to the reaction kettle, and stirred at room temperature until the modified chitosan is completely dissolved to obtain a modified chitosan solution;

[0067] Weigh dopamine, prepare an alkaline aqueous solution, add dopamine to the alkaline aqueous solution, stir and mix for 20 minutes to obtain a dispersion, and keep it warm in an ice bath for later use;

[0068] The alkaline aqueous solution is a sodium hydroxide solution, and the pH value of the sodium hydroxide solution is 11;

[0069] The mass ratio of dopamine to alkaline aqueous solution is 12 g:200 mL;

[0070] The dispersion liquid and the auxiliary agent are added to the modified chitosan solution, and the mixture is stirred and reacted for 8 hours at room temperature to obtain a chitosan-based dispersion liquid;

[0071] The mixing mass ratio of the dispersion, the additive and the modified chitosan solution is 3:0.1:15.

[0072] The modified chitosan solution is prepared as follows:

[0073] 15 g of modified chitosan was dissolved in 1% acetic acid solution to obtain a 15% (w / v) modified chitosan solution.

[0074] The preparation method of modified chitosan is:

[0075] First, 2 g of chitosan was dissolved in 1% acetic acid solution to obtain a 2% (w / v) chitosan solution;

[0076] Then, 3,4-dihydroxybenzaldehyde is added to the ethanol solution, and stirred to mix evenly to obtain a modified dispersion;

[0077] The mass fraction of the ethanol solution is 20%;

[0078] The mixing ratio of the 3,4-dihydroxybenzaldehyde and the ethanol solution is 0.15 g:10 mL;

[0079] The chitosan solution is added into the reactor, and then an inert gas is introduced into the reactor to exhaust the air in the reactor, and then the modified dispersion is obtained;

[0080] Wherein, the molar ratio of chitosan to 3,4-dihydroxybenzaldehyde in the chitosan solution is 1:1.

[0081] The inert gas is nitrogen.

[0082] The auxiliary agents are cross-linking agents, initiators and accelerators;

[0083] Among them, the crosslinking agent is MBA, the initiator is APS, and the accelerator is TEMED;

[0084] Among them, the mixing mass ratio of the crosslinking agent, the initiator and the accelerator is 10:1:1.2.

[0085] The mass ratio of quartz sand: tourmaline powder: dolomite powder: fluorite powder is 80:1:1:5.

[0086] The particle size of quartz sand is 0.2±0.1 mm.

[0087] The mixing ratio of the mixed powder and the chitosan-based dispersion is: 18g:150mL.

[0088] Drying: Place the sprayed quartz sand in a cool and ventilated place, wait for it to dry naturally, and then store it at room temperature.

[0089] Example 2

[0090] A method for preparing a defluorination seed material for a pellet reactor comprises the following steps:

[0091] (1) preparing a chitosan-based dispersion;

[0092] (2) Preparation of materials:

[0093] Weigh respectively: quartz sand, tourmaline powder, dolomite powder, fluorite powder;

[0094] (3) Dispersion mixing:

[0095] Tourmaline powder, dolomite powder and fluorite powder are mixed to obtain a mixed powder, and the mixed powder is evenly dispersed in a chitosan-based dispersion to obtain a spray coating;

[0096] (4) Spraying:

[0097] Spraying the spray coating obtained in step (3) onto the surface of quartz sand;

[0098] (5) Drying:

[0099] The sprayed quartz sand is dried to obtain the product.

[0100] The chitosan-based dispersion is prepared by:

[0101] First, an acetic acid solution is added to a reaction kettle, and then the modified chitosan is added to the reaction kettle, and stirred at room temperature until the modified chitosan is completely dissolved to obtain a modified chitosan solution;

[0102] Weigh dopamine, prepare an alkaline aqueous solution, add dopamine to the alkaline aqueous solution, stir and mix for 20 minutes to obtain a dispersion, and keep it warm in an ice bath for later use;

[0103] The alkaline aqueous solution is a sodium hydroxide solution, and the pH value of the sodium hydroxide solution is 11;

[0104] The dopamine and alkaline aqueous solution are mixed in a mass ratio of 13 g:200 mL;

[0105] The dispersion liquid and the auxiliary agent are added to the modified chitosan solution, and the mixture is stirred and reacted for 9 hours at room temperature to obtain a chitosan-based dispersion liquid;

[0106] The mixing mass ratio of the dispersion, the additive and the modified chitosan solution is 4:0.12:15.

[0107] The modified chitosan solution is prepared as follows:

[0108] 16 g of modified chitosan was dissolved in 1% acetic acid solution to obtain a 16% (w / v) modified chitosan solution.

[0109] The preparation method of modified chitosan is:

[0110] First, 2 g of chitosan was dissolved in 1% acetic acid solution to obtain a 2% (w / v) chitosan solution;

[0111] Then, 3,4-dihydroxybenzaldehyde is added to the ethanol solution, and stirred to mix evenly to obtain a modified dispersion;

[0112] The mass fraction of the ethanol solution is 20%;

[0113] The mixing ratio of the 3,4-dihydroxybenzaldehyde and the ethanol solution is 0.15 g:10 mL;

[0114] The chitosan solution is added into the reactor, and then an inert gas is introduced into the reactor to exhaust the air in the reactor, and then the modified dispersion is obtained;

[0115] Wherein, the molar ratio of chitosan to 3,4-dihydroxybenzaldehyde in the chitosan solution is 1:1.

[0116] The inert gas is nitrogen.

[0117] The auxiliary agents are cross-linking agents, initiators and accelerators;

[0118] Among them, the crosslinking agent is MBA, the initiator is APS, and the accelerator is TEMED;

[0119] Among them, the mixing mass ratio of the crosslinking agent, the initiator and the accelerator is 10:1:1.2.

[0120] The mass ratio of quartz sand: tourmaline powder: dolomite powder: fluorite powder is 85:2:3:7.

[0121] The particle size of quartz sand is 0.2±0.1 mm.

[0122] The mixing ratio of the mixed powder and the chitosan-based dispersion is: 19g:150mL.

[0123] Drying: Place the sprayed quartz sand in a cool and ventilated place, wait for it to dry naturally, and then store it at room temperature.

[0124] Example 3

[0125] A method for preparing a defluorination seed material for a pellet reactor comprises the following steps:

[0126] (1) preparing a chitosan-based dispersion;

[0127] (2) Preparation of materials:

[0128] Weigh respectively: quartz sand, tourmaline powder, dolomite powder, fluorite powder;

[0129] (3) Dispersion mixing:

[0130] Tourmaline powder, dolomite powder and fluorite powder are mixed to obtain a mixed powder, and the mixed powder is evenly dispersed in a chitosan-based dispersion to obtain a spray coating;

[0131] (4) Spraying:

[0132] Spraying the spray coating obtained in step (3) onto the surface of quartz sand;

[0133] (5) Drying:

[0134] The sprayed quartz sand is dried to obtain the product.

[0135] The chitosan-based dispersion is prepared by:

[0136] First, an acetic acid solution is added to a reaction kettle, and then the modified chitosan is added to the reaction kettle, and stirred at room temperature until the modified chitosan is completely dissolved to obtain a modified chitosan solution;

[0137] Weigh dopamine, prepare an alkaline aqueous solution, add dopamine to the alkaline aqueous solution, stir and mix for 20 minutes to obtain a dispersion, and keep it warm in an ice bath for later use;

[0138] The alkaline aqueous solution is a sodium hydroxide solution, and the pH value of the sodium hydroxide solution is 11;

[0139] The mass ratio of dopamine to alkaline aqueous solution is 15 g:200 mL;

[0140] The dispersion liquid and the auxiliary agent are added to the modified chitosan solution, and reacted for 10 hours under stirring at room temperature to obtain a chitosan-based dispersion liquid;

[0141] The mixing mass ratio of the dispersion, the additive and the modified chitosan solution is 5:0.16:15.

[0142] The modified chitosan solution is prepared as follows:

[0143] 17 g of modified chitosan was dissolved in 1% acetic acid solution to obtain a 17% (w / v) modified chitosan solution.

[0144] The preparation method of modified chitosan is:

[0145] First, 2 g of chitosan was dissolved in 1% acetic acid solution to obtain a 2% (w / v) chitosan solution;

[0146] Then, 3,4-dihydroxybenzaldehyde is added to the ethanol solution, and stirred to mix evenly to obtain a modified dispersion;

[0147] The mass fraction of the ethanol solution is 20%;

[0148] The mixing ratio of the 3,4-dihydroxybenzaldehyde and the ethanol solution is 0.15 g:10 mL;

[0149] The chitosan solution is added into the reactor, and then an inert gas is introduced into the reactor to exhaust the air in the reactor, and then the modified dispersion is obtained;

[0150] Wherein, the molar ratio of chitosan to 3,4-dihydroxybenzaldehyde in the chitosan solution is 1:1.

[0151] The inert gas is nitrogen.

[0152] The auxiliary agents are cross-linking agents, initiators and accelerators;

[0153] Among them, the crosslinking agent is MBA, the initiator is APS, and the accelerator is TEMED;

[0154] Among them, the mixing mass ratio of the crosslinking agent, the initiator and the accelerator is 10:1:1.2.

[0155] The mass ratio of quartz sand: tourmaline powder: dolomite powder: fluorite powder is 90:3:5:9.

[0156] The particle size of quartz sand is 0.2±0.1 mm.

[0157] The mixing ratio of the mixed powder and the chitosan-based dispersion is 20 g: 150 mL.

[0158] Drying: Place the sprayed quartz sand in a cool and ventilated place, wait for it to dry naturally, and then store it at room temperature.

[0159] Comparative Example 1: This comparative example is substantially the same as Example 2, except that the modified chitosan is replaced by untreated chitosan.

[0160] Comparative Example 2: This comparative example is basically the same as Example 2, except that the chitosan-based dispersion is replaced with a chitosan dispersion, and 15 g of modified chitosan is dissolved in a 1% acetic acid solution to obtain a 15% (w / v) chitosan dispersion solution.

[0161] Test experiment:

[0162] The artificial simulated wastewater (average fluoride ion concentration is about 150 mg·L -1 , pH is about 5), and the same pellet reactor containing equal amounts of the embodiment and comparative example seed crystals was used for treatment, and the fluoride ion content in the treated wastewater was compared, and the treatment defluorination rate was calculated. The results are shown in Table 1.

[0163] Table 1

[0164] Fluoride removal rate% Example 1 99.0 Example 2 99.8 Example 3 99.2 Comparative Example 1 95.2 Comparative Example 2 91.8

[0165] It can be seen from Table 1 that the defluorination seeds for the pellet reactor prepared in the present invention have a higher wastewater defluorination rate.

[0166] Morphological Characterization of the Pellet Reactor Seeds of Example 2

[0167] The basic structural characterization of pellet reactor seeds includes the following steps:

[0168] The basic structure of the pellet reactor seed was observed using a camera and an optical microscope. An appropriate amount of pellet reactor seed from Example 2 was weighed and laid flat on a clean white substrate, and its general structure was preliminarily characterized using a camera. Figure 1 Then, a small amount of the pellet reactor seed of Example 2 was spread on a glass slide, and its microstructure was characterized using an optical microscope, as shown in FIG. Figure 2 .

[0169] like Figure 1 As shown, the pellet reactor seeds appear dark brown to the naked eye. Figure 2 As shown, the pellet reactor seed has irregular morphology and low light transmittance. The above data show that the quartz sand surface has a sprayed composite inorganic material, indicating the successful preparation of the pellet reactor seed.

[0170] Crystallization Kinetics of Pellet Reactor Seeds in Example 2

[0171] The characterization of the kinetics of seed crystallization in a pellet reactor includes the following steps:

[0172] The morphology of pellet reactor seeds that were not crystallized, crystallized for 3 days, and crystallized for 6 days was characterized by camera and optical microscope. An appropriate amount of pellet reactor seeds was spread on a clean white substrate, and its general structure was preliminarily characterized by camera. Then a small amount of pellet reactor seeds was spread on a glass slide, and its microstructure was characterized by optical microscope, such as Figure 3 Subsequently, the images of crystal seeds on different days were quantified using imageJ software, and the thickness of the transparent layer on the surface of the seeds was measured. An average of 20 cases were randomly sampled in each group, and the data were plotted using Graphpad7.0. The crystallization kinetics formula was calculated after linear fitting.

[0173] like Figure 3 As shown in the figure, the color of the pellet reactor seed gradually changes from dark brown to grayish white over time. In addition, the microscopic level shows that a gradually thickening transparent layer emerges from the surface of the opaque seed, indicating that highly crystalline CaF2 crystals are effectively deposited on the pellet reactor seed. Figure 4 As shown, the crystal layer thickness of the pellet reactor seed can reach 0.018±0.003mm on the 3rd day, and the crystal layer thickness can reach 0.043±0.007mm on the 6th day. The crystallization kinetic formula is Y=0.0071*X-0.0009, which shows that the CaF2 crystals have a linear deposition trend on the pellet reactor seed, and the deposition rate can reach 7.1 microns / day, indicating that the pellet reactor seed prepared by the present invention has kinetic properties that meet the requirements of efficient removal and enrichment of fluoride ions.

[0174] Ultramicrostructure of the pellet reactor seed crystal after crystallization in Example 2

[0175] The ultrastructural characterization of pellet reactor seed crystallization includes the following steps:

[0176] The ultramicroscopic morphology of the pellet reactor seeds crystallized for 6 days was characterized by scanning electron microscopy. The dried pellet reactor seeds crystallized for 6 days were fixed on a conductive adhesive, sprayed with gold for 90 seconds to improve the conductivity, and the surface microstructure was observed by scanning electron microscopy at an accelerating voltage of 20 kV.

[0177] like Figure 5 As shown, a regularly interlaced crystal structure can be seen on the surface of the pellet reactor seed crystals after 6 days of crystallization, indicating that highly crystallized CaF2 is deposited on the surface of the seed crystals, indicating that the CaF2 crystallization induced by the pellet reactor seed crystals has good performance and can be used as an alternative to artificial fluorite.

[0178] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a defluorination seed material for a pellet reactor, characterized in that: The following steps are involved: (1) preparing a chitosan-based dispersion; (2) Preparation of materials: Weigh respectively: quartz sand, tourmaline powder, dolomite powder, fluorite powder; (3) Dispersion mixing: Tourmaline powder, dolomite powder and fluorite powder are mixed to obtain a mixed powder, and the mixed powder is evenly dispersed in a chitosan-based dispersion to obtain a spray coating; (4) Spraying: Spraying the spray coating obtained in step (3) onto the surface of quartz sand; (5) Drying: The sprayed quartz sand is dried to obtain the product.

2. The method for preparing a defluorination seed material for a pellet reactor according to claim 1, characterized in that: The chitosan-based dispersion preparation method is as follows: First, an acetic acid solution is added to a reaction kettle, and then the modified chitosan is added to the reaction kettle, and stirred at room temperature until the modified chitosan is completely dissolved to obtain a modified chitosan solution; Weigh dopamine, prepare an alkaline aqueous solution, add dopamine to the alkaline aqueous solution, stir and mix for 20 minutes to obtain a dispersion, and keep it warm in an ice bath for later use; The alkaline aqueous solution is a sodium hydroxide solution, and the pH value of the sodium hydroxide solution is 11; The mass ratio of dopamine to alkaline aqueous solution is 12-15 g: 200 mL; Adding the dispersion liquid and the additive to the modified chitosan solution, stirring and reacting for 8-10 hours at room temperature, to obtain a chitosan-based dispersion liquid; The mixing mass ratio of the dispersion, the auxiliary agent and the modified chitosan solution is 3-5:0.1-0.16:

15.

3. The method for preparing a defluorination seed material for a pellet reactor according to claim 2, characterized in that: The modified chitosan solution is prepared as follows: 15-17 g of modified chitosan was dissolved in 1% acetic acid solution to obtain 15-17% (w / v) modified chitosan solution.

4. The method for preparing a defluorination seed material for a pellet reactor according to claim 3, characterized in that: The modified chitosan preparation method is: First, 2 g of chitosan was dissolved in 1% acetic acid solution to obtain a 2% (w / v) chitosan solution; Then, 3,4-dihydroxybenzaldehyde is added to the ethanol solution, and stirred to mix evenly to obtain a modified dispersion; The mass fraction of the ethanol solution is 20%; The mixing ratio of the 3,4-dihydroxybenzaldehyde and the ethanol solution is 0.15 g:10 mL; The chitosan solution is added into the reactor, and then an inert gas is introduced into the reactor to exhaust the air in the reactor, and then the modified dispersion is obtained; Wherein, the molar ratio of chitosan to 3,4-dihydroxybenzaldehyde in the chitosan solution is 1:

1.

5. The method for preparing a defluorination seed material for a pellet reactor according to claim 4, characterized in that: The inert gas is any one of nitrogen and neon.

6. The method for preparing a defluorination seed material for a pellet reactor according to claim 2, characterized in that: The auxiliary agents are cross-linking agents, initiators and accelerators; Among them, the crosslinking agent is MBA, the initiator is APS, and the accelerator is TEMED; Among them, the mixing mass ratio of the crosslinking agent, the initiator and the accelerator is 10:1:1.

2.

7. The method for preparing a defluorination seed material for a pellet reactor according to claim 1, characterized in that: The mass ratio of the quartz sand: tourmaline powder: dolomite powder: fluorite powder is 80-90:1-3:1-5:5-9.

8. The method for preparing a defluorination seed material for a pellet reactor according to claim 7, characterized in that: The particle size of the quartz sand is 0.2±0.1 mm.

9. The method for preparing a defluorination seed material for a pellet reactor according to claim 1, characterized in that: The mixing ratio of the mixed powder and the chitosan-based dispersion is: 18-20g: 150mL.

10. The method for preparing a defluorination seed material for a pellet reactor according to claim 1, characterized in that: Drying: Place the sprayed quartz sand in a cool and ventilated place, wait for it to dry naturally, and then store it at room temperature.

Citation Information

Patent Citations

  • Defluorination absorbing material based on aluminum base composite oxides and its preparation method and use and special device of the preparation method

    CN101507911A

  • Method for realizing approximate zero discharge of high-fluorine-content and high-nitrogen-content battery production waste water in photovoltaic industry

    CN103936218A

  • Fluorine removal agent, preparation method thereof and method for deeply removing fluorine by using fluorine removal agent

    CN114988547A

  • Pellet directional induction seed crystal for defluorination and hardness removal technology of coal chemical industry wastewater

    CN118005163A

  • Fluorine crystallization treatment method for fluorine-containing waste water

    JP2004314009A